2016
DOI: 10.1186/s13690-016-0118-z
|View full text |Cite
|
Sign up to set email alerts
|

Prevalence of herbal medicine use and associated factors among pregnant women attending antenatal care at public health facilities in Hossana Town, Southern Ethiopia: facility based cross sectional study

Abstract: BackgroundThe use of herbal medicine has been on increase in many developing and industrialized countries. More pregnant women use herbal remedies to treat pregnancy related problems due to cost-effectiveness of therapy and easy access of these products. We sought to assess the prevalence of herbal medicine use and associated factors among pregnant women attending antenatal clinics of public health facilities.MethodsFacility based cross sectional study was conducted among 363 pregnant women attending antenatal… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
3
2

Citation Types

32
109
13

Year Published

2017
2017
2024
2024

Publication Types

Select...
7
1

Relationship

0
8

Authors

Journals

citations
Cited by 87 publications
(154 citation statements)
references
References 9 publications
32
109
13
Order By: Relevance
“…Also, the study discovered that, more than half of the respondents used other animal parts (54.3%) as CAM, which included animal fats, skin, and feathers. These findings are quite similar to the studies of Hillary 21 Laelago et al, 22 Okoronkwo et al, 18 and Onyiapat et al, 17 that all identified Biological products such as Ginger, garlic, oil, raspberry, animal skins, honey etc as the most used CAM. Onyiapat et al, 17 and Okoronkwo et al, 18 both recorded a prevalence rate of 56.0% for biological products, while Laelago et al, 22 recorded 69.8% prevalence rate for garlic, and 55.8% prevalence rate for ginger as the most used CAM.…”
Section: Discussion Of Findingssupporting
confidence: 90%
See 1 more Smart Citation
“…Also, the study discovered that, more than half of the respondents used other animal parts (54.3%) as CAM, which included animal fats, skin, and feathers. These findings are quite similar to the studies of Hillary 21 Laelago et al, 22 Okoronkwo et al, 18 and Onyiapat et al, 17 that all identified Biological products such as Ginger, garlic, oil, raspberry, animal skins, honey etc as the most used CAM. Onyiapat et al, 17 and Okoronkwo et al, 18 both recorded a prevalence rate of 56.0% for biological products, while Laelago et al, 22 recorded 69.8% prevalence rate for garlic, and 55.8% prevalence rate for ginger as the most used CAM.…”
Section: Discussion Of Findingssupporting
confidence: 90%
“…These figures are quite different compared to Hillary 21 study on "Utilization of herbal medicine during pregnancy, labour and postpartum period among women at Embu provincial general hospital" which discovered a high prevalence rate of 62.2% for women with 1-3 children, 69.7% for women with 4-7 children, 83.8% for women with 8-10 children and 100% for women with above 10 children. However, Laelago et al, 22 study took a different twist when it discovered on its own part a high prevalence rate of 76.1% of herbal use among women with 1-2 children, 18.3% among women with 3-4 children and 5.6% among women with above four children (Table 1 below for the summaries of CAM use by socio-demographic profiles of pregnant women in other studies). This study also revealed that the most commonly used plant products were bitter kola (29.3%), closely followed by unripe fruits (20.4%).…”
Section: Discussion Of Findingsmentioning
confidence: 99%
“…The study by Tariku et al [8] showed that 73.1% of women had used herbal medicines during pregnancy and while Dabaghian Hashem al found a 67% of the 600 pregnant women who had used at least one of the herbal medicines during their current pregnancy or earlier [9]. But the study by Krysell shows a 9% prevalence in canada [6].…”
Section: Discussionmentioning
confidence: 99%
“…The use of herbal medicine has been on the increase in many developing countries [38]. The developed countries have also shown an increased interest and use of herbal drugs due to public dissatisfaction with the cost of prescription drugs and interest in returning in to natural remedies [37,39].…”
Section: The Role Of Herbal Medicines In Management Of Hypertensionmentioning
confidence: 99%
“…This is primarily due to the cultural acceptability of healers and local pharmacopeia, the relatively low cost of traditional medicine and poor access to modern health facilities [38][39][40][41][42][43]. The use of medicinal plants for the treatment of hypertension is very common among nonindustrialized nations due to their easy availability and low cost than novel pharmaceuticals [44].…”
Section: The Role Of Herbal Medicines In Management Of Hypertensionmentioning
confidence: 99%